Clergy Well-being: The Role of Lived Values and Values Fit. Issue 1 (March 2021) - Rosales, Aaron; Fung, Joey; Lee, Cameron
This study examined the role of both valued living and person–organization values-fit in clergy well-being utilizing an archival sample of 845 Wesleyan clergy in a cross-sectional survey design. Linear regression analysis indicated that clergy successfully living out their values in ministry work was associated with higher ratings of flourishing and lower ratings of burnout. Furthermore, mediation analyses indicated that job engagement is one of the mechanisms for both these main effects. Additionally, moderation analyses indicated that the degree of values fit between clergy and their congregation moderated the association between valued living and flourishing such that valued living was most important in environments of poor fit. Overall, this exploratory study offers important insights into the multiple roles of values in clergy well-being and provides the foundation for further investigation. Implications of the findings, as well as clinical considerations for promoting valued living with clergy, are discussed.